Case study as a learning opportunity among nursing students in a university - Jackie M.L. Malesela (AOSIS, 2009)
The South African Qualification Authority Act (58/1995) requires that the facilitators of the education and training programme for nursing students implement teaching strategies that facilitate critical reflective thinking and lifelong learning. This article seeks to report fourth-year nursing students' experiences regarding the use of a case study approach as a learning opportunity. Much has been documented about the case study as an effective strategy to facilitate learning. A purposive convenience sampling method was used to select 24 nursing students in a South African university. Descriptive naïve sketches were used to collect data. The results were analysed using the content data analysis method (Burns & Grove 2003). Measures to ensure the trustworthiness of the study were taken in accordance with Lincoln and Guba's (1985) principles. Ethical standards for research were observed in order to maintain the integrity of the research. The research findings suggest that the case study as a learning opportunity is effective in facilitating learning, as indicated by the following three categories: increase in critical thinking skills, increased theory and practice integration and increased growth in presentation skills. These categories were conceptualised using the relevant literature in order to describe research-based recommendations regarding the use of a case study approach as a learning opportunity. It is recommended that facilitators involved in the nursing education programme make use of a case study approach as a learning opportunity at all levels of the nursing education programme. Opsomming Die Suid Afrikaanse Qualification Authority Act (58/1995) vereis dat die fasiliteerders van die onderrig en opleiding program vir verpleegkunde studente onderrig strategië implimenteer wat kritiese reflektiewe denke en lewenslange leer fasiliteer. Die dokument poog om 4de jaar verpleegkunde studente se leerervaring in verband met gevalle-studie benadering te rapporteer. Baie is al gedokumenteer oor die kern van die gevalle-studie as 'n effektiewe strategie om leer te fasiliteer. Die doelgerigte gerieflikheids monster metode was gebruik om 24 verpleegkunde studente in 'n Suid Afrikaanse universiteit te kies. Deskriptiewe, naïve sketse was gebruik om inligting te versamel. Resultate was ge-analiseer deur middel van die inhoud data analiese metode (Burns & Grove 2003). Mates om die vertrouens-waardigheid van die studie te verseker was gevolg volgens Lincoln en Guba (1985) se beginsels. Etiese standaarde vir navorsing was waargeneem om die integriteit van die navorsing te verseker. Navorsings bevindinge dui daarop dat die gevalle-studie as leer geleentheid effektief was in die fasilitering van leer, soos aangedui deur die volgende drie kategorië: vermeerdering van kritiese denke vaardighede; vermeerderde teorie en praktyk integrasie en vermeerderde groei in aanbiedings vaardighede. Hierdie kategorië was gekonseptualiseer deur die gebruik van toepaslike literatuur sodat navorsings-gebaseerde aanbevelinge in verband met gevalle-studie benadering as leer geleentheid beskryf kon word. Dit word aanbeveel dat fasiliteerders betrokke by die verpleeg onderrig program gebruik maak van gevalle-studie benadering op alle vlakke van die verpleeg program.